Diagnostic utility of measuring serum amyloid A with a latex agglutination turbidimetric immunoassay in bovine mastitis: Comparison with haptoglobin and alpha 1 acid glycoprotein - OTSUKA, Marina (J Vet Med Sci, 2020)
This study established the precision and accuracy of a modified latex agglutination turbidimetric immunoassay (LATIA) reagent, and evaluated the ability of the measurement of serum amyloid A (SAA) compared to haptoglobin and α1-acid glycoprotein, which are acute phase proteins (APPs), for diagnosis of clinical mastitis. Concentrations of APPs in cows with mastitis were significantly higher than those in healthy cow. Only the plasma SAA concentration in cows with clinical mastitis (44.90 mg/l; n=15) was significantly higher than that in those with subclinical mastitis (10.70 mg/l; n=16), enabling their diagnosis in contrast to other APPs. Thus, the SAA assay using a LATIA reagent is useful in assessing mastitis severity due to its higher sensitivity and specificity than other APP assays.